Ecotoxicity of Cholinium-Based Deep Eutectic Solvents - de Morais, Paulo
Deep eutectic solvents (DES) are mixtures of hydrogen bond acceptors (HBA) and hydrogen bond donors (HBD) with a melting point much lower than that of either of its components. They have been the focus of interest in past years due to their unique properties, low cost, and wide range of applications. Despite the attention given to DES and their claimed benignity when compared with ionic liquids, their environmental impact is poorly characterized and understood. In this work, the toxicity of some DES prepared with cholinium chloride ([Chol]Cl) as HBA and organic acids, namely acetic, citric, lactic, and glycolic acids, as HBD was measured with the Microtox toxicity test. These DES showed an intermediate toxicity when compared with the respective starting materials and can be considered as \"moderately toxic,\" their toxicity being clearly dominated by the concentration of the acid. They are also shown to be more toxic than their corresponding ionic liquids, namely cholinium glycolate, cholinium acetate, cholinium dihydrogencitrate, and cholinium lactate. Further studies are necessary on the ecotoxicology and biodegradability of DES, namely to evaluate their capability to both classic solvents and ionic liquids. green\" character and their alternative capability to both classic solvents and ionic liquids.